Peningkatan Kemampuan Guru Reguler dalam Deteksi Dini dan Pengembangan Program Belajar Siswa Berkebutuhan Khusus di Surabaya - Najway Azka Ar-Robbaniy; Iwan Wahyu Widayat (Universitas Nurul Jadid, 2024)
Inclusive education remains a challenging program to implement ideally, requiring ongoing management to continuously foster inclusivity in schools through various efforts. This service program aims to enhance the understanding of regular teachers in inclusive schools regarding the characteristics, early detection skills, and the development of learning programs for students with special needs. This is based on the principle that each student has unique needs, with some requiring special assistance from accompanying teachers. The program uses a needs analysis method, involving interviews and questionnaires to identify the needs of the teachers. Based on the analysis results, intervention objectives are set and a training program is designed. The intervention was conducted over two days: the first day focused on psychoeducation about inclusive education and understanding the characteristics of students with special needs, while the second day consisted of training in early detection and the preparation of specialized learning programs. The results of the intervention showed an improvement in teachers' ability to identify students' functional difficulties in physical, cognitive, and behavioral aspects. Teachers were also able to classify the characteristics of students with special needs and develop appropriate learning programs. This psychoeducation and early detection skills training effectively equips teachers in inclusive schools to be more optimal in identifying and designing learning programs for students with special needs.